The Analysis of Ambiguity Found in T.S. Eliot's Poems - Yuliani, Iya Mai; Oktoviandry, Rifki (English Language and Literature, 2024)
This research aimed to analyze the ambiguity found in T.S. Eliot’s poetry. This research was focused on Eliot words such as “The Love Song of J.Alfred Prufrock,” “The Hollow Men,” “Ash Wednesday,” “The Waste Land,” and “Gerontion.” This research used qualitative descriptive methods to discuss the ambiguity of analysis contained in T.S. Eliot’s poetry. The data was analyzed used Katz’s (1971) theory of ambiguity. The result found ambiguity divided into three types, namely structural, referential and lexical ambiguity. This research was identified types of ambiguity in the data, then explains how ambiguity occurs in the data. The research results show that lexical ambiguity frequently occurs in T.S. Eliot’s poetry rather than structural and referential ambiguity. In this study, phonetic ambiguity was not found in T.S. Eliot’s poems.